Renin-angiotensin-aldosterone pathway modulators in chronic kidney disease: A comparative review - Saeed Alshahrani (Frontiers Media S.A., 2023)
Chronic kidney disease presents a health challenge that has a complex underlying pathophysiology, both acquired and inherited. The pharmacotherapeutic treatment options available today lower the progression of the disease and improve the quality of life but cannot completely cure it. This poses a challenge to the healthcare provider to choose, from the available options, the best way to manage the disease as per the presentation of the patient. As of now, the recommended first line of treatment to control the blood pressure in chronic kidney disease is the administration of renin-angiotensin-aldosterone system modulators. These are represented mainly by the direct renin inhibitor, angiotensin-converting enzyme inhibitors, and angiotensin II receptor blockers. These modulators are varied in their structure and mechanisms of action, hence showing varying treatment outcomes. The choice of administration of these modulators is determined by the presentation and the co-morbidities of the patient, the availability and affordability of the treatment option, and the expertise of the healthcare provider. A direct head-to-head comparison between these significant renin-angiotensin-aldosterone system modulators is lacking, which can benefit healthcare providers and researchers. In this review, a comparison has been drawn between the direct renin inhibitor (aliskiren), angiotensin-converting enzyme inhibitors, and angiotensin II receptor blockers. This can be of significance for healthcare providers and researchers to find the particular loci of interest, either in structure or mechanism, and to intervene as per the case presentation to obtain the best possible treatment option.